Peningkatan keterampilan teknik dasar lay up melalui audio visual dalam permainan bola basket - Ali, Annisa Dina; Maulana, Firman; Nugraheni, Wening (Universitas Hamzanwadi, 2023)
The problem of this research is the lack of basic lay-up techniques in the Garuda Sukabumi basketball club. This study aims to determine the increase in basic lay-up technique skills through audio-visual media in basketball games. This type of research is qualitative with the action research method and the research design uses the Kemmis and Taggart spiral models. The population of this research is 20 people taken by purposive sampling technique. This research was conducted in 10 meetings with a lay-up training process using audio-visual media, in which the initial test (pretest) was carried out for the first meeting, then the second to ninth meetings were given actions and for the tenth meeting, the final test was carried out (posttest). . Based on data processing, the results of the research during the training process in cycle I were that the participants experienced an increase in the lay-up movement, the increase in the training process for the participants in the lay-up movement can be seen from the results of the instrument test on the lay-up movement through audio-visual media and got 83% of the meeting first to the 10th meeting in cycle I. In conclusion, the training process is given easily and the knowledge of lay up increases.